Socioeconomic, Behavioural, and Health-related Characteristics of Older Adults - Suvedi, Bal Krishna; Karmacharya, Isha; Karkee, Shiba Bahadur; Myia, Salau Din; Ghimire, Saruna; Karki, Kshitij; Singh, Devendra Raj; Paudel, Shishir; Marasine, Nirmal Raj; Pandey, Saloni; Adhikari, Raksha; Kafle, Bhawana; et al. (Journal of Nepal Health Research Council, 2024)
Background: The global aging population is growing rapidly, and Nepal is no exception. This increase is driven by changes in socioeconomic conditions, health behaviours, and advancements in the health system. In Nepal, almost a quarter of the national population are older adults (â‰¥45 years), whose health status is rarely elaborated. This study was carried out to assess the socioeconomic, behavioural, and health-related characteristics of older adults in Nepal. Methods: A community-based cross-sectional study was conducted among 4,179 randomly selected older adults residing in Bagmati Province from July 2022 to June 2023, via a multi-stage sampling technique. A semi-structured questionnaire including Geriatric Depression Scale, Activity of Daily Living, and Instrumental Activity of Daily Living along with sociodemographic and health profiles were used for the data collection through face-to-face interviews. The data were described in frequency and percentage across the local levels (urban/rural) and gender. Chi-square tests were done for bivariate analyses. Results: The mean age of the population was 61.66Â±11.1 years. The prevalence of multimorbidity, disability, and depression was found to be 27.6%, 23.3%, and 35.1% respectively. There was no significant difference between multimorbidity and depression across local levels, while there was a significant difference across disability status. There was a significant difference between multimorbidity and depression across genders. Conclusions: This study provides comprehensive insights into the socioeconomic status, behavioural factors, and health status of older adults in Nepal. Study findings can inform interventions and policies at local levels to consider the unique needs of the older population in Nepal. Keywords: Chronic diseases; depression; disability; Nepal; older adults.